Analyzed Quality Question of Final Exam Whole Semester on Biology Course Class XI IPA SMA Negeri District South of Solok Selatan Academic Year 2015/2016 - Ayunda Friatma; Syamsurizal Syamsurizal; Helendra Helendra (Bioeducation Journal, 2017)
Researcher conducted a study with the aim to determine the quality of items in terms of analysis: 1) the validity of the content and empirical, 2) reliability, 3) level of difficulty, 4) distinguishing features, and 5) the function of detractors. This research is a descriptive study. The sample was a set of second semester final exam subjects biology grade XI IPA SMAof the school year 2015/2016 in the south region district solok. Quantitative analysis was performed by using Anates, while for the qualitative analysis carried out by the study table. Based on the results of data analysis, the result for the review of aspects: 1) the validity of the content, about 7.5% did not meet the material aspect, 40% of questions that do not meet aspects of construction, and 77.5% did not meet aspects of language problems, and validity empirically, 52.5% are invalid matter, 2) reliability, the test has a value of 0.67 belong to the category enough, 3) the level of difficulty, 5% classified as very easy matter, 22.5% easy, 40% about the medium, 17 , 5% about the difficult, and 15% about the very difficult, 4) different power, 15% of matter which is classified as very bad, 15% about the relatively ugly, 30% about enough, and 40% items good, 5) function options, for options that are not qualified humbug is 75% and the quality is 25%. It can be concluded that the end of the semester exam subjects biology grade XI of the school year 2015/2016 in the south region district solok not meet both criteria.